Formulasi Kebijakan Kampung Zakat Terpadu Kementerian Agama (Studi Kasus Jember) - Mahfiyah Mahfiyah (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2019)
Ministry of Religious Affairs of Jember Regency develops a Kampung Zakat Terpadu (Integrated Zakat Village) in Pace, Jambearum Village, Sumberjambe Sub-District, Jember Regency. As the first zakat village in East Java Province, Kampung Zakat Terpadu in Jember also become a pilot village by the Ministry of Religious Affairs of East Java Province Regional Office. This paper tries to describe the model of policy formulation for the management of this Desa Zakat Terpadu through the descriptive qualitative approach. By doing interviews, observation, and documentation, this study finds the policy formulation model of Kampung Zakat Terpadu is influenced by preference and external factors. Then, the model of policy formulation for the management of Kampung Zakat Terpadu includes collection, distribution, utilization, and supervision.